Morphological and biochemical properties of garlic (Allium sativum L.) collections: Characterization of garlic collections - Tripathi, P C; Jadhav, H M; Qureshi, A A; Sankar, V; Mahajan, V; Lawande, K E (Journal of Spices and Aromatic Crops, 2021)
Garlic (Allium sativum L.) is an important constituent of many of traditional medicines. The nutrient composition and biochemical ingredients of garlic vary among varieties and locations. The current experiment was conducted with 35 genotypes of garlic to study variation in morphological and biochemical properties among these genotypes. The weight of bulbs ranged from 6.9 g to 22.6 g. Highest number of clove bulb-1 was recorded in collection -286 (44.6) followed by GG-2 (40.6). Clove weight was higher in collection - 316 (1.41 g). The dry weight ranged from 28.6 per cent to 38.65 per cent. Highest total soluble solids were found in collection -79 (35.1°Brix). Potassium, iron and zinc content were higher in GG-2 (1.70%, 47 ppm and 19.2 ppm, respectively). Sulphur and copper content were higher in G-41. Manganese content ranged from 6.90 to 23.1 ppm. Highest anthocyanin pigment was found in the peel of cv. Godavari (5.35 mg). There was not much difference in anthocyanin content in pulp of purple and white colour varieties. Pyruvic acid content ranged from 20.9 µ mol ml-1 to 24.9 µ mol ml-1. Over all cvs. G-50, G-41, collection -316 were found superior over others.